The hydrophobicities of cholera toxin, tetanus toxin and their components. - Ward, W H (1981)
1. Charge-shift electrophoresis showed that cholera toxin and its subunits have no hydrophobic surfaces. 2. Amino-acid composition and sequence data suggested that the proteins have no masked hydrophobic regions. 3. The A subunit of cholera toxin may interact with polar molecules in the membrane to exert its effect inside the cell. 4. The only hydrophobic part of tetanus toxin was the H-chain.